ASPEK POLITIK HUKUM DARI UU NOMOR 38 TAHUN 1999 TENTANG PENGEOLAAN - Nur Mohamad Kasim (Universitas Negeri Gorontalo, 2009)
Zaqat (Tithe) is one of the obligatory essential principles of every moeslim. It is giving to the person who is deserved for it becouse despite tithe is a potential donation (in particularly to decrease the poverty) also have a role in solving the citizensṕroblem. Using number 38, 1999, zaqatś processing will be more organized, good administration, so it will be easy in monitoring and assuring the supplying of money which is fair and apportionment. So the legitimating will get the response and encouraging from moeslim.